PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPENUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS Vd SDN 184 PEKANBARU - Hendri Marhadi (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2014)
The problem in this research was students’ achievement in fifth graderes (Vd) SDN 184 Pekanbaru still low with average value 68,63 (with KKM 70). The purpose of this research was to improve the students’ achievement of the fifth graderes (Vd) SDN 184 Pekanbaru with the implementation of cooperative learning model type Numbered Head Together (NHT). This research was an classroom action research with two cycles in second semester 2013/2014. After implementation of cooperative learning model type Numbered Head Together (NHT), students’ achievement average on test I was 72,50 that improved 5,63% from pre test with average 68,63. Students’ achievement average on test II was 86,16 that improved 25,54%. Teacher’s activity with the implementation of cooperative learning model type Numbered Head Together (NHT) in first meeting of first cycle was 70,00% (good category), and 76,16% (good category) in second meeting that improved 6,16 point. At second cycle, teacher’s activity in first meeting was 91,66% (verygood category) that improved 15,5 point from second meeting of first cycle. It got 95,83% (verygood category) in second meeting, which improved 4,17 point. Students’ activity in first meeting of first cycle was 66,66% (good category), and 70,83% (good category) in second meeting that improved 4,17 point. At second cycle, students’ activity in first meeting was 76,16% (good category) that improved 5,33 point from second meeting of first cycle. Finally, it got 91,66% (verygood category) in second meeting, which improved 15,5 point. So, the implementation of cooperative learning model type Numbered Head Together (NHT) can improved students’ achievement of fifth graderes (Vd) SDN 184 Pekanbaru.Key Words: Cooperative learning type NHT, student’s achievement, student’s activity, teacher’s activity.